Effectiveness of a community organizing intervention on mortality and its equity among older residents in Japan: A JAGES quasi-experimental study. (March 2022) - Haseda, Maho; Takagi, Daisuke; Stickley, Andrew; Kondo, Katsunori; Kondo, Naoki
Abstract: Interventions that involve key aspects of community organizing, such as quantitative community assessments and organizational partnership support for the community, may promote residents' health. We evaluated the effectiveness of this form of intervention on mortality and its variability across individual-level household equivalized income tertiles, comparing 52, 858 residents aged 65 and above in 12 intervention municipalities to 39, 006 residents in nine control municipalities in Japan. During 1, 166 days of follow-up, the adjusted hazard ratio for cumulative mortality among men in the intervention municipalities was 0.92 (95% confidence interval: 0.86, 0.99) compared to those in the control group, with similar results being observed across all income levels. Active utilization of data to evaluate communities and building intersectoral partnerships might lower older male residents' mortality risk, regardless of their income status. Highlights: Male mortality was lower where researchers used data to support the health sector. The effects of lowering mortality risk were observed across every income group. Community organizing might be healthful for older men regardless of their income.